Short-term maximal performance, alertness, dietary intake, sleep pattern and mood states of physically active young men before, during and after Ramadan observance - Hsouna, Hsen; Abdessalem, Raouf; Boukhris, Omar; Trabelsi, Khaled; Chtourou, Lassaad; Tahri, Nabil; Engel, Florian; Shephard, Roy J.; Chtourou, Hamdi (PLOS ONE, 2019)
Purpose: To assess changes in short-term maximal performance, alertness, dietary intake, sleep pattern and mood states of physically active young men before (BR), during and after Ramadan observance. Methods: Twelve physically-active men (age: 21.9±2.4yrs, height:1.77±0.09m, body-mass: 72.6±7.8kg, exercising: ≥3h/week) performed the 5-jump and the digit-cancellation (alertness) tests 15-days BR, on the first (FR) and last 10-days of Ramadan (ER) and 10-days (AR10) and 20-days (AR20) after Ramadan. During each period, sleep pattern (Pittsburgh-Sleep-Quality-Index (PSQI)), mood states (Profile-of-Mood-States (POMS)) and dietary intake were recorded. Results: No significant changes in the 5-jump, digit-cancellation test and POMS parameters appeared during and after Ramadan relative to BR. However, the PSQI total score was lower during FR compared to AR10 (p<0.001). Specifically, the subjective sleep quality was lower (i) at BR compared to FR (p<0.05), AR10 (p<0.01) and AR20 (p<0.01) and (ii) at ER and AR20 compared to FR (p<0.05). The sleep duration (i) increased at FR (p<0.05) and (ii) decreased at AR10 (p<0.01) and AR20 (p<0.05) compared to BR. Sleep disturbances were significantly greater (i) at BR compared to FR (p<0.01), ER (p<0.01), AR10 (p<0.05) and AR20 (p<0.05) and (ii) at AR10 and AR20 compared to FR and ER (p<0.05). In terms of diet, the fractional contribution of carbohydrate (%) was lower and the dietary fat content (g) was higher during ER than AR10 and AR20 (p<0.05). Further, the dietary protein (in %) was significantly lower during FR compared to BR (p<0.01), ER (p<0.05), AR10 (p<0.05) and AR20 (p<0.05). Conclusion: Ramadan had no-adverse effects on the 5-jump performance, alertness, or mood states in physically active young men. However, the sleep duration was shorter and the sleep quality was improved following compared to during Ramadan. The fractional intake of fat also increased at the expense of carbohydrate during Ramadan, and the protein intake was lower at the beginning of Ramadan than before, at the end of and after Ramadan.
Gesehen am 23.10.2019